Кризис сопротивления в несвязных средах при внутренней суффозии, обусловленной действием линейных источников (дрен-увлажнителей) - Поляков, В.Л. (Видавничий дім "Академперіодика" НАН України, 2007)
Based on an axisymmetric model of hydrodynamic deformations, the theoretical study of the abrupt initial fall in resistance to a groundwater flow from the solid component of a porous medium (resistance crisis) due to the internal piping caused by a linear source is performed. The effect of model parameters on the source intensity is analyzed for two typical natural media (mineral and organic suffosive soils).